The mapping of commodity certifications in sustainable procurement - Naranjo Clemente, Esthela Solange (2018)
Sustainability requires a high level of traceability, as many organisations do not have visibility over their supply chains, it is difficult to trace all the actors involved in the network, especially considering that supply networks are getting more complex over time. Certifications have been gaining popularity within the commodity industry to ensure environment preservation, good condition for producers and workers, as well as decreasing poverty levels. Therefore, companies are now labelling their products to show their ethical and environmental certifications to gain more acceptance within consumers and to avoid bad press from NGOs and media.